On reachability and controllability for a Volterra integro-dynamic system on time scales - DOS SANTOS, Iguer Luis Domini; TIKARE, Sanket (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
The paper studies and relates the notions of reachability and controllability for the Volterra integro-dynamic system on time scales. More specifically, we obtain necessary and sufficient conditions for reachability and controllability. In addition, we obtain an equivalence between the concepts of reachability and controllability studied. Mathematics Subject Classification (2010): 45D05, 34N05, 93B03, 93B05. Received 01 March 2024; Accepted 20 March 2024.